Improved mapping of sea ice production in the Arctic Ocean using AMSR-E thin ice thickness algorithm - Iwamoto, K; Ohshima, KI; Tamura, T (2014)
New and improved estimates of sea ice production in the Arctic Ocean are derived from AMSR-E satellite and atmospheric reanalysis data for the period 2002-2011, at a spatial resolution of 6.25 km and using a newly developed fast-ice mask. High ice production in the major coastal polynyas is well demonstrated. The total annual cumulative ice production in the major 10 polynya regions is about 1180Ã‚Â±70km 3. The interannual variability of the ice production for each polynya is presented during 2002-2011. No obvious relationship is noted between the ice production and the recent drastic reduction in the preceding summer Arctic sea ice extent. Most polynya regions exhibit maximum ice production in autumn (October - November), before areas offshore have been covered with consolidated pack ice. Sea ice production from October to November in the marginal ice zone of the Pacific Ocean sector is negatively correlated with summer ice extent there. The ice production from October to November of 2007 (a record minimum summer ice extent) was about twice as large as that in other years. The high ice production area shifted to higher latitudes i.e., toward the deep Canada Basin, due to the retreat of the summer ice edge. We speculate that the resultant increase in brine input could change the oceanic structure in the basin, specifically deepening the winter mixed layer. Â© 2014. American Geophysical Union. All Rights Reserved.